COMINGS AND GOINGS: UNIVERSITY STUDENTS IN CANADIAN SOCIETY, 1854-1913 (Author: Charles Morden Levi) - Gillett, Margaret (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2003)
CHARLES MORDEN LEVI. Comings and Goings: University students in Canadian society, 1854-1913. Montreal & Kingston. London, Ithica: McGill-Queen’s University Press (2003). 172 pp. 65.00. (ISBN 0-7735-2442-8).